2009
DOI: 10.1093/hmg/ddp568
|View full text |Cite
|
Sign up to set email alerts
|

Definitive hematopoiesis requires Runx1 C-terminal-mediated subnuclear targeting and transactivation

Abstract: Runx1 is a key hematopoietic transcription factor required for definitive hematopoiesis and is a frequent target of leukemia-related chromosomal translocations. The resulting fusion proteins, while retaining DNA binding activity, display loss of subnuclear targeting and associated transactivation functions encoded by the C-terminus of the protein. To define the precise contribution of the Runx1 C-terminus in development and leukemia, we created a knock-in mouse with a C-terminal truncation by introducing a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Cell-specific binding of TAL1 and associated proteins target different cohorts of genes. (Okuda et al 1996;Dowdy et al 2010) and its down-regulation in erythroid cells (Lorsbach et al 2004;North et al 2004). Other TFs that cobind frequently with TAL1 in erythroid cells are members of the pentameric complex.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-specific binding of TAL1 and associated proteins target different cohorts of genes. (Okuda et al 1996;Dowdy et al 2010) and its down-regulation in erythroid cells (Lorsbach et al 2004;North et al 2004). Other TFs that cobind frequently with TAL1 in erythroid cells are members of the pentameric complex.…”
Section: Discussionmentioning
confidence: 99%
“…and Goldfarb, 2007;Ito, 2008;Dowdy et al, 2010], the mechanism directing the tissue-specific expression of the non-rearranged human RUNX1 gene remains unclear. This gene was shown to be highly active in the haematopoietic system but not in other tissues (brain, lung, ovaries and testis) [Levanon et al, 1994Nucifora and Rowley, 1995].…”
mentioning
confidence: 99%
“…1316 No structures of this domain have been solved, although computational analysis 17 predicts that parts of the transactivation domain and an adjacent inhibitory domain are likely to be structured. Multiple proteins have been identified that interact with sequences C-terminal to the Runt domain that presumably mediate its activities.…”
Section: The Runx1 Protein - Domain Structure and Function And Imentioning
confidence: 99%